FILTERISASI MEDIA BERPORI DAN BERBUTIR DALAM PERAN SANITASI LINGKUNGAN TERHADAP AIR LIMBAH BERBASIS BAHAN ORGANIK MIE INSTAN - Tamod, Zetly E. (EUGENIA, 2005)
ABSTRACT Tamod, Z.E. 2005. Porous Medium Filters as Environmental Sanitation Instrument of Instant Noodle Plant's Liquid Waste Water Based on the Organic Mater. Eugenia 11 (1): 60-73. The Riset porous medium filters and granulate as environmental sanitation instrument of instant noodle plant's liquid waste based of organic mater as problems solution industrial plants north Sulawesi on cleaning their liquid waste so as not to contaminate the surrounding environment and on recycling or cleaning the waste in order to efficiently reuse it. Liquid waste of instant noodle consists of the organic-liquid waste based on the raw materials from agricuIturecuItivation, like : flour (contain of carbohydrate, protein, vitamin and mineral organic compounds) and coconut oil (contain of the fat acids like laurate, palmitate, and oleate). The aims of this experiment are to evaluate the ability of sand+clay and clay+charcoal dust mixtures as porous medium filters and to apply briquette in liquid waste recycling processes. Variables to be determined are suspended and soluble materials, acidity, electrical conductivity, BOD, COD, organic material, cation exchange capacity, soluble oxygen, nitrate, turbidity, particle distribution, permeability. The experiment will be designed as a Completely Randomised, 3 replicates, and 3 treatments. Among the applied treatments are sand (T1), clay (T2), 60% clay+charcoal dust mixture (T3). Analysis of variance (ANOVA), Duncan's Multiple Range Test (DMRT). The results of this research show that, the porous and grained medium from sand (T1), clay (T2) and clay + active charcoral dust mixture (T3) can be used as the environmental sanitation instrument on the Indofood instant noodle liquid waste based of organic mater. Keywords: filters, liquid waste